'Rivalling the Metropolis': cultural conflict between London and the regions c.1967–1973. Issue 4 (2nd October 2019) - Griffiths, John
ABSTRACT: As a contribution to this special issue on conflict and cultural production in twentieth century Britain, this article examines the relationship between London and the English regions in the second half of the 1960s. It argues that an excessive historical focus on the capital has been to the detriment of the regional scene. This was caused initially by journalistic accounts written in the period under consideration, which were dismissive of the regional city's contribution and which subsequent historians have reproduced in their narratives. This article moves beyond the capital to revisit the regional city of the period in order to examine the extent to which it contained the features demonstrated by London in the mid-to-later 1960s. Both the 'swinging' period of 1964–1967 and the concomitant underground (1965–1973) are considered here and the argument made that the regions rather kept pace with the capital to an extent not seen before this decade. Journalistic accounts of the cities written in the period itself were symptomatic of London-based prejudice and a regional declinist paradigm, but the reality, as far as nightlife and experimental culture were concerned was rather more positive.